The Effectiveness of the Implementation of BOS Funds in Improving the Quality of Learning Facilities at Al-Quran Middle School - H. Soro , Suharyanto; Nawawi, Rahmat; Sumarni, Sri (Civiliza Publishing, Indonesia., 2025)
This study examines the effectiveness of the implementation of School Operational Assistance (BOS) funds in improving the quality of learning facilities at SMP Al-Quran Cilengkrang, a religious-based school. This study aims to find the planning, implementation, and supervision processes of BOS fund use and identify supporting and inhibiting factors. The researcher used a case study approach. Data collection through observation methods, in-depth interviews, and document analysis. The results of the study indicate that BOS funds have made a positive contribution to the procurement and improvement of learning facilities such as classrooms, libraries, and technological devices. However , effectiveness is still limited due to the mismatch between fund allocation and actual school needs, especially due to the use of old student data and increases in the price of goods. Although the involvement of implementing actors such as principals, BOS treasurers, teachers, and school committees has been carried out in a participatory and transparent manner, budget flexibility is still an obstacle due to rigid regulations. Internal and external supervision has been running well, but several aspects of implementation still need improvement. The conclusion of this study is the importance of contextualizing BOS policies to be more responsive to the needs of Islamic-based schools.